Auto Position Solar System - Khairul Nazri, Muhammad Hafizi; Abu Bakar, Muhammad Asri; Zou, Muhammad Ezam Anwar; Johari Halim Shah, Nadira; Mohd Faizal Mohamed Nor, (Multidisciplinary Applied Research and Innovation, 2022)
The use of renewable energy is highly encouraged to solve increasing global warming. Solar panels are the best option to save electricity consumption. It’s becoming increasingly popular now, but not everyone understands the benefits and potential of this innovation. Existing solar panel systems do not make full use of available sunlight energy. For example, a statically positioned solar panel is only capable of getting the maximum amount of voltage only at a certain time. The objectives are design a prototype of an innovative solar panel system that can generate a higher amount of electricity than existing systems, build a system that constantly detects sunlight during the day and light detection system using LDR and Arduino. Build an array of solar panels that detect sunlight to produce maximum solar output. This innovative solar system uses servomotor functions, light-sensitive resistors, rechargeable batteries and others. This innovative solar system is built based on the C programming language to control the position of solar panels that move only one axis using the Arduino Uno. The system uses a light -sensitive resistor to detect the position of the sun with the brightest rays. Servomotor moves the solar panel towards the brightest sunlight and it will produce high electrical energy. The discussion began with an examination of renewable energy that is suitable for the population of Malaysia. Solar panels are suitable technology because Malaysia gets a lot of sunlight because Malaysia is a country located on the Equator. Most solar panels in malaysia are in static position. So our group took those shortcomings and made auto-position solar panels, so that solar panels could be used optimally.Our proposal is create more automated positioning solar panels in Malaysia so that solar energy can be harnessed.